Barrier protection via Toll-like receptor 2 signaling in porcine intestinal epithelial cells damaged by deoxynivalnol. (December 2016) - Gu, Min; Song, Sun; Lee, In; Ko, Seongyeol; Han, Seung; Bae, Suhan; Ji, Sang; Park, Byung-Chul; Song, Ki-Duk; Lee, Hak-Kyo; Han, Seung; Yun, Cheol-Heui
Abstract Intestinal barrier is the first line of defense inside the body and comprises intercellular tight junction (TJ) proteins that regulate paracellular permeability. Deoxynivalenol (DON), a fungal metabolite often found in the contaminated food of domestic animals, is known to impair intestinal barrier function and may be involved in intestinal inflammation. Unlike in humans and mice, the importance of Toll-like receptor (TLR) 2 expressed in porcine intestinal epithelial cells is largely unclear. Therefore, the aim of the present study was to investigate whether TLR2 stimulation enhances intestinal barrier function and protects against DON exposure. We found that the cells treated with TLR2 ligands decreased the epithelial barrier permeability and enhanced TJ protein expression in intestinal porcine epithelial cells (IPEC-J2). In addition, pretreatment with TLR2 ligand, including Pam3CSK4 (PCSK) and lipoteichoic acid fromBacillus subtilis, prevented DON-induced barrier dysfunction by increasing the expression of TJ proteins via the PI3K-Akt-dependent pathway. It is likely that the DON-disrupted intestinal barrier caused biological changes of immune cells in the lamina propria. Thus, we conducted co-culture of differentiated IPEC-J2 cells in the upper well together with peripheral blood mononuclear cells in the bottom well and found that apical TLR2 stimulation of IPEC-J2 cells could alleviate the reduction in cell survival and proliferation of immune cells. Conclusively, TLR2 signaling on intestinal epithelial cells may enhance intestinal barrier function and prevent DON-induced barrier dysfunction of epithelial cells.